IJIMAI Editor's Note - Vol. 4 Issue 6 - Verdú, Elena (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
The International Journal of Interactive Multimedia and Artificial Intelligence provides an interdisciplinary forum in which scientists and professionals can share their research results and report new advances on Artificial Intelligence and Interactive Multimedia techniques. The research works presented in this regular issue are based on various topics of interest, among which are included: nature inspired optimization algorithms, multi-agent systems, fast motion estimation, handwritten recognition, supervised and unsupervised machine learning methods, or web mining.
Keywords: editors note; IJIMAI